Agricultural Implications of the Fukushima Nuclear Accident 2013
DOI: 10.1007/978-4-431-54328-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Migration of Radiocesium Fallout in Soil in Fukushima

Abstract: The vertical migration of radiocesium fallout in the soil was monitored for 1 year at several locations in Fukushima after the nuclear power plant explosion. We determined the vertical gamma ray intensity profiles in boreholes in the soil using a scintillation survey meter with a lead collimator to restrict the incoming radiation, only allowing horizontal detection. The average migration distances of radiocesium at two time points were accurately determined based on the difference in the depth of the centroids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 4 publications
3
14
0
Order By: Relevance
“…2) agrees with other studies in orchards and undisturbed fields (Ohno et al 2012;Shiozawa 2013;Sato 2014a). The correlation between radiocesium concentration in the mature fruit and in the topsoil layer is, therefore, likely due to the fact that radiocesium is strongly retained in soil.…”
Section: Discussionsupporting
confidence: 91%
“…2) agrees with other studies in orchards and undisturbed fields (Ohno et al 2012;Shiozawa 2013;Sato 2014a). The correlation between radiocesium concentration in the mature fruit and in the topsoil layer is, therefore, likely due to the fact that radiocesium is strongly retained in soil.…”
Section: Discussionsupporting
confidence: 91%
“…3 Immediately after the FDNPP accident, Tanaka et al (2013c) reported that the radiocesium was water soluble, though once radiocesium adsorbed on to soil and rock particles it quickly became essentially insoluble. The increase in insolubility was also reported by Shiozawa (2013) who indicated that the strong fixation of radiocesium to clay particles during the initial 2e3 months after the accident reduced the migration of radiocesium in the depth profile. The strong fixation to clay particles was again reported by Saito et al (2014) and Kikawada et al (2014) who indicated that virtually no radiocesium was extractable from soil samples with simple water solutions.…”
Section: Soil Depositionsupporting
confidence: 72%
“…2). Studies in northeastern Japan after the Fukushima accident showed high radioactive Cs contents in the top layer of untilled arable soils (Koarashi et al 2012;Yamaguchi et al 2012;Shiozawa 2013). Many studies conducted after the Chernobyl accident indicated that vertical migration of radioactive Cs was very slow, and most radioactive Cs was present in the upper soil layers (e.g., Almgren and Isaksson 2006).…”
Section: Radioactive Cs In Pastures 795mentioning
confidence: 99%